A Constitution for Peace: Federalism and Consociationalism in Bosnia and Herzegovina - Aras, Francisco Ignacio (2020)
The present paper draws on the Constitution of Bosnia and Herzegovina, resulted from the Dayton Peace Agreement, in order to explain how the elements of federalism and consociationalism can become important tools in the field of transitional justice. By combining federalism and consociationalism, it will be demonstrated how shared-rule and self-rule can be useful in addressing the demands of territorially concentrated ethnic groups for more autonomy and self-government, while at the same time preserving the territorial integrity of the state. It also explains the role of post-conflict constitutional design processes on their ability to reconcile groups, to address intolerable grievances and to prevent further polarization by providing a common vision of the future of a state.